Development of a new comprehensive and reliable endometrial receptivity map (ER Map/ER Grade) based on RT-qPCR gene expression analysis - Enciso, M; Carrascosa, J P; Sarasa, J; Martínez-Ortiz, P A; Munné, S; Horcajadas, J A; Aizpurua, J (Human reproduction (Oxford), 2018)
Abstract STUDY QUESTION Is it possible to determine the receptivity status of an endometrium by combined quantitative reverse transcription PCR (RT-qPCR) expression analysis of genes involved in endometrial proliferation and immunity? SUMMARY ANSWER The new ER Map®/ER Grade® test can predict endometrial receptivity status by RT-qPCR using a new panel of genes involved in endometrial proliferation and the maternal immune response associated to embryonic implantation. WHAT IS KNOWN ALREADY The human endometrium reaches a receptive status adequate for embryonic implantation around Days 19-21 of the menstrual cycle. During this period, known as the window of implantation (WOI), the endometrium shows a specific gene expression profile suitable for endometrial function evaluation. The number of molecular diagnostic tools currently available to characterize this process is very limited. In this study, a new system for human endometrial receptivity evaluation was optimized and presented for the first time. STUDY DESIGN, SIZE, DURATION ER Map®/ER Grade® validation was achieved on 312 endometrial samples including fertile women and patients undergoing fertility treatment between July 2014 and March 2016. Expression analyses of 184 genes involved in endometrial receptivity and immune response were performed. Samples were additionally tested with an independent endometrial receptivity test. PARTICIPANTS/MATERIALS, SETTING, METHODS A total of 96 fertile women and 120 assisted reproduction treatment (ART) patients participated in the study. Endometrial biopsy samples were obtained at LH + 2 and LH + 7 days in fertile subjects in a natural cycle and at the window of implantation (WOI) in patients in a hormone-replacement therapy (HRT) cycle. Total RNA was purified, quality-checked and reverse-transcribed. Gene expression was quantified by high-throughput RT-qPCR and statistically analyzed. Informative genes were selected and used to classify samples into four different groups of endometrial receptivity status. MAIN RESULTS AND THE ROLE OF CHANCE Significantly different gene expression levels were found in 85 out of 184 selected genes when comparing LH + 2 and LH + 7 samples (paired t-test, P < 0.05). Gene ontology analyses revealed that cell division and proliferation, cell signaling and response, extracellular organization and communication, immunological activity, vascular proliferation, blood pressure regulation and embryo implantation are the most over-represented biological terms in this group of genes. Principal component analysis and discriminant functional analysis showed that 40 of the differentially expressed genes allowed accurate classification of samples according to endometrial status (proliferative, pre-receptive, receptive and post-receptive) in both fertile and infertile groups. LARGE SCALE DATA N/A. LIMITATIONS, REASONS FOR CAUTION To evaluate the efficacy of this new tool to improve ART outcomes, further investigations such as non-selection studies and randomized controlled trials will also be required. WIDER IMPLICATIONS OF THE FINDINGS A new comprehensive system for human endometrial receptivity evaluation based on gene expression analysis has been developed. The identification of the optimal time for embryo transfer is essential to maximize the effectiveness of ART. This study is a new step in the field of personalized medicine in human reproduction which may help in the management of endometrial preparation for embryo transfer, increasing the chances of pregnancy for many couples. STUDY FUNDING/COMPETING INTEREST(S) The authors have no potential conflict of interest to declare. No external funding was obtained for this study.